Carbon Nanofibers Coated with Silicon/Calcium-Based Compounds for Medical Application. (1st April 2019) - Smolka, Wojciech; Dlugon, Elzbieta; Jelen, Piotr; Niemiec, Wiktor; Panek, Agnieszka; Paluszkiewicz, Czeslawa; Zagrajczuk, Barbara; Menaszek, Elzbieta; Markowski, Jaroslaw; Blazewicz, Marta
Abstract : The aim of this work was to develop a method for the manufacture of carbon nanofibers in the form of mats containing silicon and calcium compounds with potential biomedical application. Carbon nanofibers (ECNF) were prepared from the electrospun polyacrylonitrile (PAN) nanofibers. The electrospun polymer nanofibers were heat treated up to 1000°C to obtain carbon nanofibers. The surface of ECNF was covered with a silica-calcium sol (ECNF+Si/Ca) by dip-coating technique followed by the stabilization process. Both types of carbon nanofibers, i.e., the as-received and covered with the sol, were tested to confirm their osteoconductive properties. Biological tests were performed, including genotoxicity, cytotoxicity, and alkaline phosphatase (ALP) activity. Morphology of adhering cells to nanofiber surface was described. The nanofibers were subjected to a bioactivity test in contact with SBF artificial plasma. Biological tests have revealed that the nanofiber-modified ECNF+Si/Ca in contact with osteoblast cells were biocompatible, and the level of cytotoxicity was lower compared to the control. The ALP activity of the modified nanofibers was higher than nonmodified nanofibers and indicates potential applications of such carbon materials in the form of mats as a substrate for bone tissue regeneration.